The intralumenal fragment pathway mediates ESCRT-independent surface transporter down-regulation - Erin Kate McNally (Nature Portfolio, 2018)
Cell surface receptors are thought to be internalized via the multivesicular bodies (MVBs) in an ESCRT-dependent pathway. Here, the authors report that in yeast, a hexose transporter is internalized via an ESCRT-independent pathway into intralumenal fragments (ILF).